River water sampling and water quality analysis - Muhamad, Mimi Suliza; Hamidon, Nuramidah; Abdul Hamid, Nor Hazren; Harun, Hasnida (Penerbit UTHM, 2020)
Nowadays, populations are increasing rapidly along with nation development. Water is scarce and the most essential resources in the world [1]. According to [2], urban areas contribute to various type of pollutants that are from point and non-point sources which degrade the water bodies. It is estimated that the consumption of fresh water by domestic usage make up 70% to 80% of the total volume of wastewater globally [3]. Concern on environmental protection has increased over the years. Monitoring of water sources are important to ensure that water is in good condition and safe for the human consumption.